Kinetic analysis of antibody responses to blastocystis hominis in sea and intestinal secretions from orally infected mice and partial characterization of target antigens - Santos, Herbert J. (Institute of Biology, College of Science, University of the Philippines Diliman, 2009)
The kinetics of antibody production against Blastocystis hominis, one of the emerging infectious protozoan parasites which causes intestinal disorder in humans and animals was studied.